Internal gene segments from a mouse-adapted influenza B virus confer increased pathogenicity to mice - Arne Matthys; Laura Amelinck; Anouk Smet; Tine Ysenbaert; Thorsten U. Vogel; Xavier Saelens; João Paulo Portela Catani (PLoS ONE, 2026)
Influenza B viruses (IBVs) contribute significantly to the annual influenza epidemics in human. Most IBV strains are non- or poorly pathogenic in mice, which are frequently used for vaccine studies. We describe the generation of a mouse-adapted IBV strain that retains pathogenicity in mice when carrying hemagglutinin (HA) and neuraminidase (NA) gene segments from a heterologous IBV strain. Serial passage of an influenza B reassortant virus, containing the HA and NA segments from B/Washington/02/2019 on a mouse-adapted B/Memphis/12/1997 backbone, resulted in the selection of an IBV that was highly pathogenic for mice. This mouse-adapted IBV strain had acquired non-synonymous mutations in 5 gene segments. Sequence analysis of the intermediate passages indicated that mutations in the matrix (M), polymerase acidic (PA), and polymerase basic 1 (PB1) gene segments appeared at passages 9 and 13, suggesting that these mutations contributed to the pathogenicity in mice. Mouse challenge studies with rescued reassortant viruses with one or multiple mutated gene segments, confirmed the importance of substitutions in the M and PA segments for pathogenicity. Using the novel mouse-adapted IBV backbone, we rescued reassortant viruses containing the HA and NA segments of B/Austria/1359417/2021 and demonstrated its increased pathogenicity in BALB/c mice compared to IBV rescued on the parental strain. This mouse-adapted IBV backbone provides a valuable tool for the study of IBV in mice.